2019
DOI: 10.4018/978-1-5225-6983-1.ch005
|View full text |Cite
|
Sign up to set email alerts
|

Creating Business Value and Competitive Advantage Through Glocalization

Abstract: Glocalization is considered as one of the main contributors to value creation and development as well as for competitive advantage enhancement on a global stage. Previous studies suggest that globalization indicates the co-presence of universal and local practices. Globalization is based on the phenomenon that products or services providers have further consideration and a sense of the locality needs and wants in foreign markets instead of the assumption that parent market practices can be applied in foreign m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Thus, the more graduates are exposed to these types of assessments instead of the seat down examination, the better their chances of acquiring employability skills. Thus, the assertion by Deeley (2014) and Alharahsheh and Pius (2019) that summative assessment influences on employability skills is upheld by this study.…”
Section: Discussion Of the Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…Thus, the more graduates are exposed to these types of assessments instead of the seat down examination, the better their chances of acquiring employability skills. Thus, the assertion by Deeley (2014) and Alharahsheh and Pius (2019) that summative assessment influences on employability skills is upheld by this study.…”
Section: Discussion Of the Resultsmentioning
confidence: 46%
“…A study by Deeley (2014) found that employability skills can be enhanced through summative assessment. Alharahsheh and Pius (2019) confirmed that summative assessment assesses key required skills, knowledge and understanding, and their overall professional development in relation to personal experiences. Thus, further studies are required to confirm further the influence of summative assessment on the acquisition of 21st-century employability skills among tertiary graduates.…”
Section: Conceptual Review and Hypothesis Developmentmentioning
confidence: 59%
“…Companies may need to rethink their pricing strategies, distribution channels, and promotional campaigns to resonate with local consumers while maintaining a cohesive brand identity across different markets. Moreover, glocalization emphasizes the importance of continuous learning and adaptation (Alharahsheh & Pius, 2019). It requires companies to stay attuned to evolving consumer trends, market conditions, and regulatory changes in each locality to remain competitive.…”
Section: What Does Glocalization Entail In This Context?mentioning
confidence: 99%
“…Currently, many students prefer working or learning away from their country of birth and, as a result, living in a globalized society (Alharahsheh & Pius, 2019a, 2020a; Helmi & Pius, 2018b). However, for them to be ready to access job opportunities, they are required to acquire subject-specific knowledge and skills to prepare them to be ready to compete in the globalized market or society (Alharahsheh & Pius, 2019b).…”
Section: Introductionmentioning
confidence: 99%